Evaluation of characteristics and performance of fabricated polysulfone/cellulose acetate ultrafiltration membrane - Wae Abdulkadir Usin, Wan Aisyah Fadilah (2018)
Ultrafiltration is a separation technique, which is specifically for biomolecular separation and it has been widely used in food and pharmaceutical industries. The performance and characteristics of fabricated ultrafiltration membrane have gained some concern in producing a new membrane with robust characteristics. Therefore, the selection of membrane material is very important to improve the membrane performance. In this study, the objectives involve development and formulations of polysulfone/cellulose acetate (PSf/CA) ultrafiltration membranes and evaluating the flux performance and the characteristics of the fabricated PSf/CA ultrafiltration membrane. This study involved three different formulations of polymer ratio, polymer concentration, and additives compositions. The polymer ratio varied into three different ratio of PSf/CA compositions, which were 90/10, 80/20, and 70/30. Meanwhile, the formulations of polymer concentration were compared with different concentrations of 15 wt. %, 17.5 wt. % and 20 wt. % and further modification was carried out for selected membrane by the additive compositions. The additives involved were polyvinylpyrrolidone (PVP), pluronic (Plu) and PVP/Plu. All the fabricated membranes were evaluated for compaction, pure water flux, hydraulic resistance, and fouling characteristic. Further, these membranes were characterized for chemical structure identification by fourier transform infrared (FTIR), morphology by scanning electron microscopy (SEM) and mechanical properties test. From overall evaluation and characterization, PSf/CA-20 membrane obtained the most uniform flux permeation and good membrane morphology but low flux recovery. However, further modification with additives composition showed that PSf/CA-PVP/Plu obtained a good flux permeation, flux recovery and satisfied polyphenol rejection. The exposure of PSf/CA-PVP/Plu membrane to the different hydraulic cleaning methods resulted in similar range of flux recovery ratio (FRR %) between 67 % to 79 % compared to the membrane with single additive; PVP or Plu. Hence, PSf/CA-PVP/Plu membrane is the more preferred membrane, which can be further applied to the related industries due to the improved morphology, which are advantages to the flux permeation and fouling resistance.